High Reversibility of “Soft” Electrode Materials in All-Solid-State Batteries - Sakuda, Atsushi; Takeuchi, Tomonari; Shikano, Masahiro; Sakaebe, Hikari; Kobayashi, Hironori (Frontiers in Energy Research, 2016)
All-solid-state batteries using inorganic solid electrolytes (SEs) are considered to be ideal batteries for electric vehicles and plug-in hybrid electric vehicles because they are potentially safer than conventional lithium-ion batteries (LIBs). In addition, all-solid-state batteries are expected to have long battery life owing to the inhibition of chemical side reactions because only lithium ions move through the typically used inorganic SEs. The development of high-energy density (more than 300 Wh kg−1) secondary batteries has been eagerly anticipated for years. The application of high-capacity electrode active materials is essential for fabricating such batteries. Recently, we proposed metal polysulfides as new electrode materials. These materials show higher conductivity and density than sulfur, which is advantageous for fabricating batteries with relatively higher energy density. Lithium niobium sulfides, such as Li3NbS4, have relatively high density, conductivity, and rate capability among metal polysulfide materials, and batteries with these materials have capacities high enough to potentially exceed the gravimetric-energy density of conventional LIBs. Favorable solid–solid contact between the electrode and electrolyte particles is a key factor for fabricating high performance all-solid-state batteries. Conventional oxide-based positive electrode materials tend to give rise to cracks during fabrication and/or charge–discharge processes. Here, we report all-solid-state cells using lithium niobium sulfide as a positive electrode material, where favorable solid–solid contact was established by using lithium sulfide electrode materials because of their high processability. Cracks were barely observed in the electrode particles in the all-solid-state cells before or after charging and discharging with a high capacity of approximately 400 mAh g−1 suggesting that the lithium niobium sulfide electrode charged and discharged without experiencing substantial mechanical damage. As a result, the all-solid-state cells retained more than 90% of their initial capacity after 200 cycles of charging and discharging at 0.5 mA cm−2.